2020
DOI: 10.1109/access.2020.3006469
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Grey Wolf Optimizer for Optimum Parameters of Multilayer Type-2 Asymmetric Fuzzy Controller

Abstract: This study presents a modified algorithm of the grey wolf optimizer to solve the problem of learning rate selection in the multilayer type-2 asymmetric fuzzy controller (MT2AFC). The improvements of our modified optimizer are: the best position of the swarm is memorized, thus making the alpha wolves only update when a better position appears in the next iteration; search performance is enhanced by giving more freedom to update the grey wolf position. The proposed optimizer algorithm is then applied to optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Le et al [147] suggested an improved GWO to overcome the learning rate determination issue in the multilayer type-2 asymmetric fuzzy controller. Two phases were suggested for improving the GWO: remembering the swarm's optimal location and enhancing the ability of the agents to search.…”
Section: ) Other Improved Versions Of Grey Wolf Optimizermentioning
confidence: 99%
“…Le et al [147] suggested an improved GWO to overcome the learning rate determination issue in the multilayer type-2 asymmetric fuzzy controller. Two phases were suggested for improving the GWO: remembering the swarm's optimal location and enhancing the ability of the agents to search.…”
Section: ) Other Improved Versions Of Grey Wolf Optimizermentioning
confidence: 99%
“…for nonlinear chaotic systems to achieve good control performance such as an adaptive fuzzy control (Sambas et al 2020), a passive control (Sambas et al 2019a), an active backstepping control (Sambas et al 2021), an adaptive control (Sambas et al 2019b), an integral sliding mode control (Vaidyanathan et al 2019), a double function-link brain emotional control (Huynh et al 2020c), a modified grey wolfbased multilayer type-2 asymmetric fuzzy control (Le et al 2020b), a self-organizing interval type-2 fuzzy asymmetric cerebellar model articulation control (Le et al 2020a), a wavelet interval type-2 fuzzy brain emotional control (Huynh et al 2020a), and a brain-imitated neural network control .…”
Section: Interval Type-2 Fuzzy Brain Emotional Control Design For the Synchronization Of 4d Nonlinear Hyperchaotic Systemsmentioning
confidence: 99%
“…for nonlinear chaotic systems to achieve good control performance such as an adaptive fuzzy control (Sambas et al 2020), a passive control (Sambas et al 2019a), an active backstepping control (Sambas et al 2021), an adaptive control (Sambas et al 2019b), an integral sliding mode control (Vaidyanathan et al 2019), a double function-link brain emotional control (Huynh et al 2020c), a modified grey wolfbased multilayer type-2 asymmetric fuzzy control (Le et al 2020b), a self-organizing interval type-2 fuzzy asymmetric cerebellar model articulation control (Le et al 2020a), a wavelet interval type-2 fuzzy brain emotional control (Huynh et al 2020a), and a brain-imitated neural network control .…”
Section: Interval Type-2 Fuzzy Brain Emotional Control Design For the Synchronization Of 4d Nonlinear Hyperchaotic Systemsmentioning
confidence: 99%